Pengaruh Model Pembelajaran Think Talk Write dengan Bantuan Gambar Terhadap Hasil Belajar Bahasa Arab Siswa Kelas VIII MTs Negeri 1 Deli Serdang - Ridho Ramadhani Fitri; Zulfahmi Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to test the effect of the Think Talk Write learning model with the help of images on the learning outcomes of Arabic students in grade VIII at MTsN 1 Deli Serdang. The method used in this study is a quantitative method with experimental techniques. After the researcher conducted research and experiments on grade VIII students at MTsN 1 Deli Serdang, the researcher found that the Think Talk Write learning media with the help of images greatly influenced student learning outcomes. The increase in learning outcome test scores when using Think Talk Write learning media with the help of images. In addition, students are also more active in learning. And based on the statistical value obtained t count 1.962 and t table 2.042 Because t count <t table, then Ho is accepted. So it can be concluded that there is a significant effect of the Think Talk Write learning model on student learning outcomes. There is a significant increase in learning outcomes with an average increase of 35 after getting a learning model using Think Talk Write. The learning that is carried out becomes interesting and fun for students. Because learning hones students to think critically, collaborate, and can share opinions among students. Learning tends not to be boring. Learning objectives can also be achieved optimally.